An easy-to-implement combinatorial approach involving an activity-based assay for the discovery of a peptidyl copper complex mimicking superoxide dismutase. Issue 3 (10th December 2019) - Vincent, Amandine; Fores, Jennifer Rodon; Tauziet, Elodie; Quévrain, Elodie; Dancs, Ágnes; Conte-Daban, Amandine; Bernard, Anne-Sophie; Pelupessy, Philippe; Coulibaly, Koudedja; Seksik, Philippe; Hureau, Christelle; Selmeczi, Katalin; et al.
Abstract : A strategy combining combinatorial chemistry and an activity-based screening leads to the development of a peptidyl catalytic drug that reduces the oxidative stress in cellular models. Abstract : A combinatorial approach using a one-bead-one-compound method and a screening based on a SOD-activity assay was set up for the discovery of an efficient peptidyl copper complex. The complex exhibited good stability constants, suitable redox potentials and excellent intrinsic activity. This complex was further assayed in cells for its antioxidant properties and showed beneficial effects when cells were subjected to oxidative stress.